2020
DOI: 10.34175/jno202003003
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Associations between Dietary Fiber Intake and Cancer Prevention or Prognosis

Abstract: The increase in tumor incidence is closely related to dietary factors. In recent years, many researchers have carried out in-depth research to investigate whether increasing the intake of dietary fiber can prevent tumors and improve the prognosis, but the results have been unclear. We herein searched the literature in common academic databases and incorporated and summarized the relevant articles. The literature clearly indicates that dietary fiber can protect against the following cancers: colorectal cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…SIDF also has excellent water-and oil-holding properties, in vitro antioxidant activity, and low price, which improves its edible value. Moreover, it has been implicated in reducing the risk of intestinal disease, cardiovascular disease, and diabetes [10][11][12]. Studies on protein-polysaccharide composite gels have revealed that these composite gels elicit better functional performance and stability than the single component gel [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…SIDF also has excellent water-and oil-holding properties, in vitro antioxidant activity, and low price, which improves its edible value. Moreover, it has been implicated in reducing the risk of intestinal disease, cardiovascular disease, and diabetes [10][11][12]. Studies on protein-polysaccharide composite gels have revealed that these composite gels elicit better functional performance and stability than the single component gel [13,14].…”
Section: Introductionmentioning
confidence: 99%